• Розв'яжіть рівняння:
    1) (х+2)(х-2)-х(х-6)=0
    2) 3х(4+12х)-(6х-1)(6х+1)=11х

Ответы 2

  • 1)(x+2)(x-2)-x(x-6)=0x²-4-x²+6x=0-4+6x=06x=0+46x=4x=4:6x=2/3Ответ:x=2/32)3x(4+12x)-(6x-1)(6x+1)=11x12x+36x²-(36x²-1)=11x12x+36x²-36x²+1=11x12x+36x²-36x²-11x=-1x=-1Ответ:x=-1
    • Автор:

      lili18
    • 5 лет назад
    • 0
  • 1)ответ: х=2/32)ответ: x=-1................
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years